Sistema de criação de rã-touro (Lithobates catesbeianus): Qualidade da água e mudanças ambientais - Mercante, Cacilda Thais Janson; Vaz-dos-Santos, André Martins; Moraes, Munique de Almeida Bispo; Pereira, Jeniffer Sati [UNESP]; Lombardi, Júlio Vicente (FapUNIFESP (SciELO), 2014)
Introduction: Frog farming, if not well managed, may cause environmental damages. The use of antibiotics, the organic discharge and the introduction of exotic species can disseminate risks such as eutrophication, changes in the water quality and organic pollution, factors that affect the human consumption. Aim: Evaluating the water quality of a bullfrog farming system, discussing their relations to production and the environment based on the current legislation. Methods: Sampling was performed on a monthly basis from November 2006 to March 2007 during growth and fattening phases of bullfrog (Lithobates catesbeianus). Sample sites were distributed according to the water flow: upstream from the mixing zone, affluent (supply water), bay, effluent, mixing zone and downstream from the mixing zone. In the field, pH, electrical conductivity, dissolved oxygen, temperature and turbidity were measured. In laboratory, nitrogen, phosphorus and chlorophyll a concentrations were analyzed. Results: The concentration of nutrients was determiner for water quality in the bay and its effluent. According to the current legislation, the effluent exceeded the limits for total phosphorus (> 0.030 mg L-1) and total nitrogen (> 1.27 mg L-1). Other variables presented acceptable values in light of the current laws. Conclusion: The high values of nutrients and other factors such as conductivity and turbidity are proportional to the animal growth due to the inadequate management practices evidenced by feed conversion rate. The following management options are proposed: maintaining the flow and decreased density of animals; maintaining the flow and density storage with adequate control of the food supply.
Bullfrog (Lithobates catesbeianus) farming system: Water quality and environmental changes
Keywords: Aquaculture; Effluent; Management; Nitrogen; Phosphorus